The contribution of the new technologies to the 21st - Century Design - M. Teresa Vasconcelos (2002)
In the past the market economy was dominated by the local and regional design,characterized for strong links to the customs, traditions and natural resources from eachregion.As the consequence of the technological advances and the growing needs of consumption,at present, products are manufactured based on economical, functional and marketingcriterions, which means that their design is very offset from the regional and local signs.Between the challenges that characterize the actual economy, one highlights the existenceof more market niches, product variations and shorter life cycles. To survive in this economy,marked by the competition and the globalisation, one search to imply in product developingprocess, the design, engineering, marketing and production department, that composes aknown industrial methodology called concurrent or simultaneous engineering.In this article, one intends to exhibit the applications and advantages of the newtechnologies, like Rapid Prototyping (RP), that are valuable tools of the concurrentengineering and to analyse the specific implications in the design history and teaching.RP is a family of modern technologies that generate three-dimensional solid objects undercomputer control. Besides its designation be reported to the first major application that isindustrial prototyping, the RP equipments also allow the rapid tooling and the directmanufacture of small series or single products.Nowadays, the commercialisation of RP equipments, termed concept modellers or 3Dprintersis in great expansion. Although these machines use a very reduced class of cheapmaterials with poor mechanical characteristics, they allow the designers to verify and quicklytest the ideas that they are developing during the creative process. The designer can realize inplenitude the iterative process of creation without the traditional economical and materialslimitations, being enough to send the CAD file directly to the RP equipment placed in aoffice, like an usual inkjet printer. So it is possible to test new ideas with better accuracybefore its concretisation, avoiding misunderstandings and delays and inciting the positivecriticism through the involvement of the technical staff from all the related departments.Particularity, faced to the challenges due to the globalisation, the traditional and regionalindustries will find in these technologies the means that they need to ensure its own futuresurviving.This presentation is divided in the following sections:- Innovation loop in the past and in the present. The iterative process.- New technologies available to the design and the designers: Rapid Prototyping andInternet.- Design Pedagogy: new challenges in the formation of future generations of designers.- Conclusions and future trends.